The internalisation of sociocultural and thin-ideal standards in sports scale: Development and preliminary validation in female athletes participating in aesthetic sports - Scoffier-Mériaux, S.; Ferrand, C.; d'Arripe-Longueville, F. (International Journal of Sport and Exercise Psychology, 2017)
Thinness is a part of today's sociocultural standards of beauty and thus is implicated in body-image dissatisfaction and eating disorders. In female aesthetic sports, thinness is a standard for aesthetics and performance. Measuring the internalisation of thin-ideal standards in these athletes may therefore help athletes, coaches, parents, administrators, sport psychologists, and so on to gain insight into the risks associated with body-image dissatisfaction and disordered eating. This study aimed to develop and validate the Internalisation of Sociocultural and Thin-Ideal Standards in Sports (ISTISS) scale. Four studies involving 357 female aesthetic athletes examined the exploratory factorial structure, temporal stability, and concurrent validity of the ISTISS, which gave rise to a 10-item scale with two subscales: internalisation of sociocultural standards and thin-ideal standards in sports. Internal consistencies were satisfactory and relationships with the self-regulation of eating attitude in sport were as expected. These findings provide preliminary evidence for the appropriateness of the ISTISS scale for female aesthetic sports athletes.